Knowledge, Attitudes, and Practices of Dental Practitioners Toward Laminate Veneer Preparation in Benghazi, Libya - Belead, Rabea; Tawati, Rania; Mohamed, Abdulla; Bogazia , Sara (AlQalam Journal of Medical and Applied Sciences, 2025)
Laminate veneers are widely used in esthetic dentistry for managing structural and discoloration defects of anterior teeth. Their success relies on proper clinical knowledge, technique, and patient-centered care. This study aimed to evaluate the knowledge, attitudes, and practice approaches of dental practitioners in Benghazi, Libya, regarding laminate veneer preparation and placement. A cross-sectional, questionnaire-based survey was conducted among 100 registered dental practitioners, with 99 complete responses analyzed. The 15-item questionnaire assessed awareness of veneer techniques, materials, clinical practices, and associated complications. Responses were scored and analyzed using SPSS, with chi-square tests applied to identify associations with clinical experience. Most practitioners demonstrated moderate knowledge regarding veneer preparation, with 77.8% aware of alternatives for fluorosis management and 74.7% familiar with veneer thickness guidelines. Awareness of recent material advances was lower (51.5%). Only 47.5% attended veneer-related courses. Debonding was the most reported complication (48.5%). Statistically significant associations were found between experience and specific knowledge areas, such as alternative treatment awareness [p = 0.008] and cementation techniques (p=0.002). While general awareness of veneer preparation was acceptable, gaps remain in specialized training and continuing education, highlighting the need for targeted professional development initiatives.